2006
DOI: 10.1111/j.1471-0528.2006.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and polycystic ovary syndromes in indigenous South Asian women with previous gestational diabetes mellitus

Abstract: Objective To determine the risk of metabolic syndrome (MS) and polycystic ovary syndrome (PCOS) in a cohort of indigenous South Asian women with a recent history of gestational diabetes mellitus (GDM).Design Case-control study.Setting Department of Obstetrics & Gynaecology, University of Colombo, Sri Lanka.Sample Two hundred and seventy-four indigenous Sri Lankan women with previous GDM and 168 ethnically matched controls. Of these, 147 with previous GDM and 67 controls not taking hormonal contraception partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It is noteworthy, that despite no significant difference in the individual risk factors, a past history of GDM was significantly higher among those with early diagnosed GDM. This supports our hypothesis of the high probability for a larger proportion of women in the early diagnosed group of GDM to have had previously undetected chronic diabetes / pre-diabetes as many groups including us have shown that nearly 40-60% of those with previous GDM progress into chronic diabetes and the metabolic syndrome, as early as 3 years post partum (7,17,18,19). It is also interesting that those with clear PGDM in this study had a significantly lower BMI.…”
Section: Discussionsupporting
confidence: 86%
“…It is noteworthy, that despite no significant difference in the individual risk factors, a past history of GDM was significantly higher among those with early diagnosed GDM. This supports our hypothesis of the high probability for a larger proportion of women in the early diagnosed group of GDM to have had previously undetected chronic diabetes / pre-diabetes as many groups including us have shown that nearly 40-60% of those with previous GDM progress into chronic diabetes and the metabolic syndrome, as early as 3 years post partum (7,17,18,19). It is also interesting that those with clear PGDM in this study had a significantly lower BMI.…”
Section: Discussionsupporting
confidence: 86%
“…39 Studies conducted in the United States identified indigenous women as Native American, 27 American Indian, Alaskan Native, 38 or Pima Indian. 31,32,35 Studies in Sri Lanka identified women as Indigenous South Asian women 33,36 and the study in New Zealand identified women as either Maori or Pacific Islander. 34 None of the studies involving indigenous women in Australia or Sri Lanka included a comparison group of nonindigenous women.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
“…34 Sample selection methods varied widely. Four studies used retrospective clinical audits of patient records, 27,34,36,38 three studies collected clinical data, 32,35,39 and three used data from community studies. 28,29,33 One study recruited via convenience sampling, 37 while another utilized geographically defined purposive sampling.…”
Section: Characteristics Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations